The Measurement of PM10 and PM2.5 Concentration for Outdoor and Indoor Surrounding Industrial Area - Hamzah, Nurhidayah; Mohd Kamil, Nor Amani Filzah; Maznan, Nurul Syafiqah (Journal of Advancement in Environmental Solution and Resource Recovery, 2021)
The industrial area located adjacent to UTHM main campus releases air pollutants to the surrounding area.  In addition, high complaints were received from UTHM's residents and surrounding area due to air pollution from the industrial area.  The main objective of this study is to measures PM10 and PM2.5 concentration for indoor and outdoor building in UTHM main campus and surrounding industrial area in Parit Raja, Batu Pahat, Johor.  Air sampling was conducted to determine the indoor and outdoor concentrations of PM10 and PM2.5.  The highest concentration (40.8 ug/m3 and  29.1 ug/m3 for PM10 and PM2.5 respectively) was at Tun Dr Ismail Residential College for outdoor concentration.  Whereas, Bestari Residential College shows the lowest concentration (14.2 ug/m3 and 10 ug/m3 for PM10 and PM2.5 respectively).  Results from this study found that outdoor air pollution did not affect the indoor air pollution.  For further improvement, the number of sampling stations need to be increased especially high rise buildings in UTHM main campus.